1974
DOI: 10.1111/j.1471-4159.1974.tb10750.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐dependent Efflux and Exchange of Gaba in Synaptosomes

Abstract: Abstract— The influx and efflux of [3H]GABA were investigated in synaptosomes. Two efflux components were detected. The first, termed spontaneous efflux, was not affected by the external sodium chloride concentration. The second, termed GABA‐stimulated efflux, was observed when low levels of GABA were added to the incubation medium and was found to require external sodium chloride. The rate of spontaneous efflux at 0°C was about 37 per cent of the rate at 27°C but both GABA‐stimulated efflux and GABA influx we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
31
0
1

Year Published

1976
1976
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(39 citation statements)
references
References 25 publications
7
31
0
1
Order By: Relevance
“…Direct measurements ofthe concentrations of GABA with an amino acid analyzer confirmed our suggestion that net uptake of [I4C]GABA was primarily responsible for the observed accu-'c2000- (26), who reported an increase in the concentration ofthis amino acid in the supernatant when preloaded synaptosomes were diluted in a medium containing unlabeled GABA. The inability of these authors to show net uptake of GABA may be attributed either to the quality of their synaptosomal preparations or to the methods used to separate the synaptosomes from the medium or to a combination ofboth.…”
Section: Resultssupporting
confidence: 61%
“…Direct measurements ofthe concentrations of GABA with an amino acid analyzer confirmed our suggestion that net uptake of [I4C]GABA was primarily responsible for the observed accu-'c2000- (26), who reported an increase in the concentration ofthis amino acid in the supernatant when preloaded synaptosomes were diluted in a medium containing unlabeled GABA. The inability of these authors to show net uptake of GABA may be attributed either to the quality of their synaptosomal preparations or to the methods used to separate the synaptosomes from the medium or to a combination ofboth.…”
Section: Resultssupporting
confidence: 61%
“…As in ganglia, BALA is an effective substrate for the glial carrier and causes an accelerated efflux of [3H1-GABA from olfactory cortical slices (Brown & Scholfield, unpublished observations). L-2,4-Diaminobutyric acid (DABA) is a good substrate for the synaptosomal (presumed neural) carrier (Iversen & Johnston, 1971;Simon & Martin, 1973;Kelly, Dick & Schon, 1975), and accelerates GABA-efflux from brain synaptosomes (de Belleroche & Bradford, 1972;Simon et al, 1974). BABA has also been reported to accelerate the release of GABA from synaptosome preparations (de Belleroche & Bradford, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…(b) Addition of carrier-substrates has been observed to accelerate the efflux of GABA from central nervous system preparations (Cutler, Hammerstad, Cornick & Murray, 1971;de Belleroche & Bradford, 1972;Simon, Martin & Kroll, 1974;Levi & Raiteri, 1974;Raiteri, Federico, Colethi & Levi 1975). When measured under comparable experimental conditions the rate coefficients for resting and substratestimulated efflux of [3H]-GABA from isolated mammalian olfactory cortex slices are equal to or exceed those for the corresponding release from ganglia (Brown & Scholfield, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…For example, for 'y-aminobutyric acid (GABA), no evidence for an exocytotic release has been provided, and the mechanism of reuptake is still under discussion (8)(9)(10)(11)(12)(13)(14)(15). In fact, several recent studies in vitro have shown that GABA transport consists essentially of a 1:1 homoexchange process in nerve endings incubated in standard media in the presence of low concentrations of the amino acid (9)(10)(11)(12)(13)(14). This finding does not seem to fit with the high-affinity reuptake theory for inactivation of synaptically released GABA (4,6,16) and raises the question of the functional significance of a transport system that does not result in a net translocation of the substrate in one or the other direction.…”
mentioning
confidence: 99%